Conceptual design and implantation of an external fixator with improved mobility for knee rehabilitation. Issue 8 (11th June 2017) - Gatti, Gianluca
Abstract: A hinged external fixator is used to allow early knee rehabilitation in case of injury or trauma, as an alternative approach to immobilization. It is mainly adopted for the treatment of dislocations, which involve tearing of the ligaments, and it basically consists of two links connected to each other by a revolute joint. Each link is fixed to the femur and tibia via pin fixation, and the revolute joint is approximately aligned to the knee flexion-extension (FE) axis. The advantage in its implantation is to protect ligament reconstruction, while allowing for an aggressive rehabilitation. Traditional fixators only accommodate the functional flexion movement in a limited range, i.e. where the anatomical movement is closer to a planar circular trajectory. This paper presents the conceptual design and implantation procedure of a double-axis fixator, which accommodates both FE and longitudinal internal-external rotation. The procedure is based on accurate knee kinematics measurements and on computer-aided multibody simulations to assist clinicians in the implantation. An experimental test is presented using an artificial knee, and guidelines are given for in vitro studies. The proposed technique may allow for a better understanding of knee kinematics and have the potential advantage to increase the range of motion in postoperative rehabilitation.